Listening to Islam with Thomas Merton, Sayyid Qutb, Kenneth Cragg and Ziauddin Sardar : praise, reason and reflection - Watson, John H., 1939- (Sussex Academic Press, 2005)
Christianity and Islam are capable of dialogue. Neither faith has a single religious establishment or narrow belief system, both are rainbows of faith and practice. This book offers evidence of the complexities and rewards of exchanging ideas and opinions on the development and necessity of Islamic-Christian interfaith understanding.